Lone parents, time-limited in-work credits and the dynamics of work and welfare - Mike Brewer; Jonathan Cribb (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Time-limited in-work credits are cheaper, and more targeted, than conventional in-work credits, but are thought to have small to zero long-term impacts. We study two time-limited in-work credits in- troduced in the mid-2000s in the UK and find they reduced welfare participation and increased employment. Both policies increased job retention once recipients were in work and boosted employment even after the payments were stopped. Conditioning on hours of work was important. Paying a credit to those working 16+ hours a week only increased part-time work, while conditioning on full-time work reduced part-time work and increased full-time work.
Keywords: H21; I38; 330; in-work credits; time-limits; duration model